2009
DOI: 10.3322/caac.20039
|View full text |Cite
|
Sign up to set email alerts
|

Patient Decision Aids for Prostate Cancer Treatment: A Systematic Review of the Literature

Abstract: Treatment decision-making can be difficult and complex for patients with low-risk prostate cancer. To the authors' knowledge, there is no consensus regarding an optimal treatment strategy and the choice of therapy involves tradeoffs between differing harms and benefits that are sensitive to patient values. In such situations, patients are often asked to participate actively in the decision-making process, and high-quality decisions require a well-informed patient whose values and preferences have been taken in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(113 citation statements)
references
References 58 publications
3
110
0
Order By: Relevance
“…And although many patients require time to process information about a cancer diagnosis before considering options, most feel pressure to make a decision about treatment soon after diagnosis (whether it results from system-level issues or pressure placed by the patient on him-or herself) [27,28]. As a result of the decision complexity, communication challenges, patients' heightened emotional state, and time pressure to make a decision, many patients unfortunately make decisions without fully understanding the options and associated risks and benefits [27][28][29]. In some cases, this lack of knowledge can lead to an underuse or overuse of cancer treatments [30,31].…”
Section: The Process Of Shared Decision Making In Oncology Practicementioning
confidence: 99%
“…And although many patients require time to process information about a cancer diagnosis before considering options, most feel pressure to make a decision about treatment soon after diagnosis (whether it results from system-level issues or pressure placed by the patient on him-or herself) [27,28]. As a result of the decision complexity, communication challenges, patients' heightened emotional state, and time pressure to make a decision, many patients unfortunately make decisions without fully understanding the options and associated risks and benefits [27][28][29]. In some cases, this lack of knowledge can lead to an underuse or overuse of cancer treatments [30,31].…”
Section: The Process Of Shared Decision Making In Oncology Practicementioning
confidence: 99%
“…Decision aids are available throughout the field of medicine, in both cancer and non-cancer populations (examples at https:// decisionaid.ohri.ca/AZlist.html). Within oncology, das have been reported in the context of cancer screening and in the selection of treatment in the adjuvant and definitive settings 9,[14][15][16] . The hallmarks of the cancer das include facilitating communication, aiding in the decision-making process, and enhancing patient satisfaction 9,10 .…”
Section: Discussionmentioning
confidence: 99%
“…Another systematic review of decision aids for prostate cancer treatment identified 10 observational trials not included in the Cochrane review (30). These studies were generally quasi-experimental with pre-post design, though two used controls, one concurrent (31) and the other historical (32).…”
Section: Effectiveness Of Decision Aidsmentioning
confidence: 99%